RAID Level 6 and Level 6+ Reliability - Thomas Johannes Emil Schwarz (International Journal of Applied Sciences and Smart Technologies, 2020)
Storage systems are built of fallible components but have to provide high degrees of reliability. Besides mirroring and triplicating data, redundant storage of information using erasure-correcting codes is the only possibility to have data survive device failure.We provide here exact formula for the data-loss probability of a disk array composed of several RAID Level 6 stripes. This two-failure tolerant is not only used in practice but can also provide a reference point for the assessment of other data organizations.